Penentuan Harga Pokok Produksi Berdasarkan Sistem Activity Based Costing pada Perusahaan Meubel PT. Wood (Universitas Negeri Semarang, 2015)
The calculation of cost of goods sold is a very important activity undertaken by any company. In the calculation of cost of goods sold which is right, then the selling price of a product can be known and specified precisely so that the products are not overcost and also not undercost. The object of this research is the cost that became the focus of activity on Furniture Company PT Wood World to determine the allocation of the cost of raw materials, labor costs and factory overhead costs that are charged to the product. The result was the cost of goods sold with Activity Based Costing system on the furniture cabinets greater than conventional system (undercost). Cost of production using Activity Based Costing system in the furniture chairs less then conventional system (overcost).